Antifouling paint schemes for green SHIPS. (1st February 2019) - Mukherjee, A.; Joshi, M.; Misra, S.C.; Ramesh, U.S.
Abstract: Recent advances in antifouling (AF) paints in general prevent fouling in about 95% of the vessel's immersed surface. However the remaining area which amounts to 5% or less of the total area does get fouled. Although this level of fouling has marginal impact on the routine performance of the vessel it is a predominant vector for the transmigration of invasive species which is now a serious environmental concern. Virtually all ocean going vessels are coated with antifouling paints predominant among them are "Self polishing coatings". CFD analysis conducted on various types of vessels have indicated that there are certain "hotspots" where the polishing rates are exceedingly high and would polish the AF paints at a much faster rate and ultimately result in the failure of the AF coating. A possible solution to this issue is to first identify these hotspots and suitable paint schemes/formulations are to be applied in such areas. An experimental procedure utilizing a "drum-test" apparatus can be used to compute the coating thicknesses based on wall shear stresses. Such painting schemes would prevent the premature failure of the AF coating in general and significantly reduce the risk of transmigration of invasive species in particular. Highlights: A theoretical procedure has been suggested for determining wall shear stress on the underwater hull surface. There appears to be a correlation between high shear stresses and antifouling paint depletion on ship's hull. A methodology has been suggested to coat ship's hull appropriately to minimize the risk of Antifouling film failure.